2009
DOI: 10.2337/db08-0875
|View full text |Cite
|
Sign up to set email alerts
|

Exenatide Sensitizes Insulin-Mediated Whole-Body Glucose Disposal and Promotes Uptake of Exogenous Glucose by the Liver

Abstract: OBJECTIVE-Recent progress suggests that exenatide, a mimetic of glucagon-like peptide-1 (GLP-1), might lower glycemia independent of increased ␤-cell response or reduced gastrointestinal motility. We aimed to investigate whether exenatide stimulates glucose turnover directly in insulin-responsive tissues dependent or independent of insulinemia.RESEARCH DESIGN AND METHODS-An intraportal glucose infusion clamp was used in dogs to measure glucose turnover to encompass potent activation of the putative glucose/GLP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
31
1
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 52 publications
3
31
1
1
Order By: Relevance
“…In another study in dogs, net hepatic glucose uptake was increased marginally by Ex-4 under hyperglycemic hyperinsulinemic conditions during a somatostatin clamp (67). A possi- ble explanation for the discrepancy between that study and the present study is that in the former study insulin was infused into a peripheral vein during somatostatin infusion.…”
contrasting
confidence: 51%
See 1 more Smart Citation
“…In another study in dogs, net hepatic glucose uptake was increased marginally by Ex-4 under hyperglycemic hyperinsulinemic conditions during a somatostatin clamp (67). A possi- ble explanation for the discrepancy between that study and the present study is that in the former study insulin was infused into a peripheral vein during somatostatin infusion.…”
contrasting
confidence: 51%
“…In contrast, when insulin is infused into a peripheral vein, portal levels are slightly lower than arterial levels (53). Thus, although arterial insulin levels increased from basal almost fivefold during the clamp in the study by Zheng et al (67), portal vein insulin concentrations would have increased less than twofold. Therefore, it is possible that Ex-4 may potentiate the effects of insulin action on liver glucose uptake during a smaller rise in hepatic insulin levels, whereas the physiological liver insulin levels generated by mild hyperglycemia in the present study may have been saturating in regard to an insulinEx-4 interaction.…”
mentioning
confidence: 58%
“…For instance, increased microvascular perfusion in muscle could lead to increased glucose uptake, a beneficial phenomenon which was shown in rodents and dogs. 3,29 In our study, we observed insulin-independent reductions in glucose levels after exenatide infusion, which could be explained by increased muscle glucose disposal rate. However, in this study, we did not assess this by using labeltracer techniques.…”
mentioning
confidence: 56%
“…Thus, the function of GLP-1 is not limited to the islets. The extrapancreatic actions of GLP-1 include inhibition of gastric emptying, regulation of appetite and satiety, suppression of glucose production, and promotion of hepatic glucose uptake (2,4,20,23,25,27).…”
Section: Discussionmentioning
confidence: 99%